The Importance of Input-Output Analysis in Advancing Sustainable Agricultural Development in Hulu Sungai Selatan Regency - Mohammad Arliyan Syahrial; Monika Handayani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores the role of input-output (I-O) tables in promoting sustainable agricultural sector development in Hulu Sungai Selatan Regency, Indonesia. The agricultural sector is a critical component of the local economy, contributing significantly to the Gross Regional Domestic Product (GRDP) and providing employment for the majority of the population. However, the sector faces challenges such as climate change, unsustainable farming practices, and limited access to modern agricultural technologies. By utilizing I-O tables, this research analyzes the interdependencies between the agricultural sector and other economic sectors, identifying opportunities for growth and the potential impact of sustainable practices. The findings reveal that integrating sustainable agricultural practices can enhance productivity, increase farmers' income, and contribute to environmental preservation. Policy recommendations are provided to support the adoption of sustainable methods, including incentives for environmentally friendly practices, education and training for farmers, and the development of supporting infrastructure. The study underscores the importance of data-driven approaches in formulating effective policies that promote both economic growth and sustainability in the agricultural sector.